The present and future disease burden of hepatitis C virus (HCV) infection with today's treatment paradigm. (May 2014) - Razavi, H.; Waked, I.; Sarrazin, C.; Myers, R. P.; Idilman, R.; Calinas, F.; Vogel, W.; Mendes Correa, M. C.; Hézode, C.; Lázaro, P.; Akarca, U.; Aleman, S.; et al.
Summary: The disease burden of hepatitis C virus (HCV) is expected to increase as the infected population ages. A modelling approach was used to estimate the total number of viremic infections, diagnosed, treated and new infections in 2013. In addition, the model was used to estimate the change in the total number of HCV infections, the disease progression and mortality in 2013–2030. Finally, expert panel consensus was used to capture current treatment practices in each country. Using today's treatment paradigm, the total number of HCV infections is projected to decline or remain flat in all countries studied. However, in the same time period, the number of individuals with late‐stage liver disease is projected to increase. This study concluded that the current treatment rate and efficacy are not sufficient to manage the disease burden of HCV. Thus, alternative strategies are required to keep the number of HCV individuals with advanced liver disease and liver‐related deaths from increasing.